Nitrogen, irrigation, and alley management effects on nitrate leaching from raspberry. Issue 1 (30th July 2020) - Kuchta, Shawn; Neilsen, Denise; Forge, Thomas; Zebarth, Bernie J.; Nichol, Craig
Abstract: High NO3 concentrations in the Abbotsford‐Sumas aquifer are linked to raspberry ( Rubus idaeus L.) production. Passive capillary wick samplers were used to quantify the impacts of N, irrigation, and alley managements on drainage and NO3 leaching from raspberry rows and alleys over 4 yr. Conventional management (100 kg N ha −1 surface broadcast on the row as a split application, clean cultivation of alleys, and fixed‐duration drip irrigation) was compared with different mineral fertilizer N rates, N applied as manure, alleys seeded to a perennial forage grass or an autumn‐seeded spring barley ( Hordeum vulgare L.) crop, or evapotranspiration (ET)‐scheduled irrigation. The temporal pattern of drainage and NO3 leaching was driven by seasonal precipitation and growing season irrigation. Growing season drainage and NO3 leaching were much lower under ET‐scheduled irrigation compared with fixed irrigation. Nitrate leaching was high (up to 90 kg N ha −1 ), even with no managed N inputs due to high inherent soil fertility and large quantities of N applied in irrigation water. Nitrate leaching was insensitive to N fertilizer rate. Application of N as poultry manure more than doubled NO3 leaching compared with fertilizer, emphasizing the need to use organic N inputs judiciously. The perennial grass alley cover crop resulted in the greatest overall reduction in NO3 leaching. Our data indicate that no single management strategy is sufficient to protect groundwater quality. Rather, an integrated package of improved practices (i.e., application of a reduced rate of mineral N through fertigation, combined with ET‐scheduled irrigation and perennial alley crop) is necessary to protect groundwater quality. Core Ideas: Nitrate leaching from the root zone was high and insensitive to fertilizer N rate. Poultry manure greatly increased NO3 leaching compared with fertilizer. ET‐scheduled irrigation reduced growing season drainage and NO3 leaching. Perennial grass alley crop reduced NO3 leaching from the alley. An integrated package of improved practices is necessary to reduce leaching.